A Revisit to the Safe Haven Properties of Gold: Empirical Evidence from the Chinese stock market - TANG, Xiaohui (2021)
Based on the literature review, this paper analyzes and explores the correlation between gold and Chinese stock returns, which may be positive, negative, and time-varying. That is, gold can hedge Chinese stock market risk as a safe-haven asset; gold cannot hedge Chinese stock market risk as a safe-haven asset; the ability of gold to hedge risks in Chinese stock market is time-varying. Based on the theoretical basis of cointegration test, Granger causality test, static coefficient analysis, GARCH, DCC-GARCH, etc., this article examines gold from December 4, 2012, to August 20, 2021, from the perspectives of static phased and dynamic overall (London Gold) and the correlation between the Shanghai Composite Index. This paper divides the data into a bull market period and a bear market period, and a bull market and a bear market as a division interval. It is more practical to play the role of hedging in different turbulent periods. Furthermore, through the cointegration theory and Granger causality test, it could get whether there is a positive or negative linkage effect between the two assets, and then it could easily deduce the correlation of the market returns of the two assets. The result found no long-term equilibrium cointegration relationship between gold and the Chinese stock market, nor Granger causality. In addition, through the static phased static factor coefficients and the dynamic factor coefficients of the overall dynamic analysis, it can be found that the overall data is generally positive. Even if negative values occasionally appear in the dynamics, they are very short-lived. Therefore, gold is not an effective and appropriate safe-haven asset to hedge the risks of the Chinese stock market.